The creation of a community the city of Wells in the Middle Ages - Shaw, David Gary 1962- (Oxford historical monographs, 1993)
He explores the importance of the family, the extent of social mobility, the position of women, and the roles of conviviality on the one hand, and religion on the other, in shaping communal activity and communal spirit. Dr Shaw makes full use of the rich archives of Wells to present in vivid and telling detail the anatomy of a medieval borough